Drugs in psychiatric practice - Tyrer, Peter J. (London ; Boston : Butterworths, 1982)
Drugs in Psychiatric Practice present a comprehensive examination of the drug treatment in psychiatry. It discusses certain ways in which drugs behaved. It addresses the advances in pharmacology and the basis of prescription. Some of the topics covered in the book are the classification of psychotropic drugs; basic principles of pharmacokinetics and drug metabolism; anti-schizophrenic drugs; evaluation of psychotropic drugs; unconventional chemotherapy; anti-parkinsonian and anti-dyskinetic drugs; introduction of amitriptyline; and tricyclic antidepressants. The role of tricyclic drugs in the.
Introduction and historical aspectsPharmacology; Pharmacokinetics; Determination of lithium concentration; Lithium preparations; Clinical use; Treatment of depression with lithium; Lithium and schizoaffective disorders; Lithium and other conditions; Unwanted effects; Drug interactions; Unwanted and toxic effects of lithium; Acknowledgements; References; Chapter 11. Psychostimulants; Introduction; Pharmacology; Pharmacokinetics; Clinical efficacy; Methylphenidate; Other psychostimulants; Drug interactions; References; Chapter 12. Drugs of dependence; Controlled drugs; Opiate drugs.
ReferencesChapter 6. Antianxiety drugs; Generalized central anxiolytics (sedative drugs); Specific central anxiolytics (ataractic drugs); Combined preparations including antianxiety drugs; Peripheral anxiolytics; Comparison of antianxiety drugs; References; Chapter 7. Tricyclic antidepressants; Introduction; Pharmacology; Pharmacokinetics; Clinical use; Introduction of amitriptyline; Other tricyclic antidepressant drugs; Comparisons between tricyclic drugs and other antidepressive treatments; Tricyclic drugs in the treatment of enuresis; General topics concerning the tricyclic drugs.
Electronic reproduction.
Print version record.
Keywords: Psychotropic drugs